2018
DOI: 10.1371/journal.pone.0202742
|View full text |Cite|
|
Sign up to set email alerts
|

Individual- and community-level determinants of child immunization in the Democratic Republic of Congo: A multilevel analysis

Abstract: Understanding modifiable determinants of full immunization of children provide a valuable contribution to immunization programs and help reduce disease, disability, and death. This study is aimed to assess the individual and community-level determinants of full immunization coverage among children in the Democratic Republic of Congo. This study used data from the Demographic and Health Survey 2013–14 from the Democratic Republic of Congo. Data regarding total 3,366 children between 12 and 23 months of age were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 41 publications
37
44
1
Order By: Relevance
“…The PAF value in the 2016 survey showed that if measles immunization coverage in all subgroups were at the same level as household with mothers who have secondary school education or higher, the overall country’s measles immunization coverage could be improved by a staggering 45%. Similar findings were reported by other studies in Ethiopia [ 42 ], Democratic Republic of Congo [ 43 ] and Nigeria [ 44 ]. Educated mothers are more likely to use health care services (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The PAF value in the 2016 survey showed that if measles immunization coverage in all subgroups were at the same level as household with mothers who have secondary school education or higher, the overall country’s measles immunization coverage could be improved by a staggering 45%. Similar findings were reported by other studies in Ethiopia [ 42 ], Democratic Republic of Congo [ 43 ] and Nigeria [ 44 ]. Educated mothers are more likely to use health care services (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…The other finding in this study was that children born at a health facility had higher Odds of being fully immunized compared to children born at home. This finding was in line with the studies done in Zimbabwe (28) and Democratic Republic Congo (20). The reason might be women utilized institutional delivery service, be more confident in utilizing child immunization services.…”
Section: Discussionsupporting
confidence: 89%
“…The reason might be women utilized institutional delivery service, be more confident in utilizing child immunization services. And also administrative of the BCG vaccine soon after childbirth and counseling at a health facility might have contributed to being knowledgeable on children's vaccination (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the community level, the geographic region and place of residence, communities with high illiteracy rates, socioeconomically disadvantaged communities, communities with a higher rate of institutional delivery, and maternal antenatal care were associated with childhood vaccination status. 26,27 However, a preponderance of these studies focused on either complete vaccination or incomplete vaccination and few studies have examined the predictors of childhood vaccination using a three-way category of full vaccination, under-vaccination, and non-vaccination. Similarly, prior studies conducted in Malawi on childhood vaccination have focused either on coverage of individual vaccines or complete and incomplete, vaccination and no study separated the vaccination status into non-, under, and full e vaccination.…”
Section: Introductionmentioning
confidence: 99%